Gravity wave effects on postsunset equatorial F region stability. Issue 7 (18th July 2014) - Hysell, D. L.; Jafari, R.; Fritts, D. C.; Laughman, B.
Abstract The influence of gravity waves on the stability of the postsunset equatorial F region ionosphere is investigated numerically. For this investigation, we use the output of a direct numerical simulation of waves and turbulence in the mesosphere and lower thermosphere to force a simulation of ionospheric dynamics. Both simulations are cast in three dimensions. The effectiveness of the neutral‐plasma coupling involved is generally thought to depend on the dynamo efficiency and spatial resonance of the forcing, which we evaluate. In our simulations, the postsunset equatorial ionosphere could be deformed by neutral waves after 5–15 min most severely when the wavefronts were aligned approximately with the magnetic meridian, despite the fact that the dynamo efficiency is modest even in that case. However, poor spatial resonance limits the subsequent growth of the deformations in our simulations, and the seeding of interchange instabilities does not occur. The coupled simulations predict the formation of intermediate layers in the equatorial valley region (150–250 km apex altitude) under some circumstances that could serve as telltales in nature of the presence of the kind of neutral forcing we simulate.